2022
DOI: 10.1080/0886022x.2022.2032746
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Circ-Snrk ameliorates apoptosis and inflammation in acute kidney injury by regulating the MAPK pathway

Abstract: Background Circular RNA (circRNA) is involved in the process of acute kidney injury (AKI), but only a few circRNAs have been reported. In the study, we investigated a new circRNA and its association with AKI. Methods An AKI model was established in Sprague-Dawley rats, followed by serum creatinine and urea nitrogen tests measured by a biochemical analyzer. The pathological changes and apoptosis in the renal tissue were detected by Hematoxylin and Eosin, and TUNEL staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Two studies found that CircRNAs mediated the development of ischemic AKI 15,16 . In the current study, we demonstrated that circRNA_45478 promoted renal cell apoptosis during ischemic injury.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Two studies found that CircRNAs mediated the development of ischemic AKI 15,16 . In the current study, we demonstrated that circRNA_45478 promoted renal cell apoptosis during ischemic injury.…”
Section: Discussionsupporting
confidence: 64%
“…Two studies reported that circ-Snrk and mmu_circ_0000943 mediated the development of ischemic AKI. 15,16 Between them, circ-Snrk mediated the renal cell apoptosis during ischemic injury. 15 In the present study, we showed that cir-cRNA_45478 was an apoptosis driver during ischemic injury, which was supported by the following evidences:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NRK-52E rat kidney epithelial cells exposed to hypoxia and reperfusion showed increased expression of circ-SNRK, which was shown to participate in the activation of the MAPK signalling pathway and promoting cell apoptosis and secretion of TNF-α and IL-6. Knockdown of circ-SNRK resulted in the reduction in renal inflammation and improvement in the serum creatinine and urea levels [ 50 ]. Conversely, circ-YAP1 was downregulated in AKI patients and in HK-2 cells subjected to IRI conditions.…”
Section: Circrna Expression In Aki Due To Ischaemia-reperfusion Injurymentioning
confidence: 99%